Chapter Mining Digital Music Score Collections: Melody Extraction and Genre Recognition - Iñesta, José M. (InTechOpen, 2008)
In the field of computer music, pattern recognition algorithms are very relevant for music information retrieval (MIR) applications. Two challenging tasks in this area are the automatic recognition of musical genre and melody extraction, having a number of applications like indexing and selecting musical databases. One of the main references for music is its melody.